Pengaruh Social Media Marketing Activities Terhadap Purchase Intention dengan Relationship Quality, Brand Awareness, dan Perceived Value - Selsa Mahfuza Budiani; Fajar Satria (Masyarakat Ekonomi Syariah Bogor, 2026)
The use of social media as a source of information before purchasing, especially by Generation Z and Millennials who dominate the Indonesian local skincare market, requires brands to manage Social Media Marketing Activities effectively in order to influence Purchase Intention amidst the dynamics of rapidly changing digital trends. This study aims to analyze the influence of Social Media Marketing Activities on Purchase Intention with Relationship Quality, Brand Awareness, and Perceived Value of Generation Z and Millennial consumers in the Indonesian local skincare industry. This study uses a quantitative approach with a dare survey method to 207 respondents of social media users in the Jabodetabek area who have seen or engaged such as following, liking, commenting, or sharing social media content from local Indonesian skincare accounts, namely Somethinc, Azarine, Wardah. The analysis technique uses the Partial Least Squares Structural Equation Model (PLS-SEM) method through SmartPLS 4 software. The results of this study indicate that Social Media Marketing Activity, Relationship Quality, Brand Awareness, and Perceived Value have a significant positive effect on Purchase Intention. These findings provide insight into the importance of social media marketing activities that can build emotional bonds, enhance brand recognition, and shape perceived value, thus increasing purchase intention. Companies are advised to strengthen perceived value through content that demonstrates superior product value and responsive interactions on social media to increase purchase intention.